Evaluating Chemical/Oil Tanker Investments using DEMATEL and ANP: A Case Study in PT ABC - Hendriyadi, Hendriyadi; Ciptomulyono, Udisubakti; Dinariyana, Anak Agung Bagus (Journal Research of Social Science, Economics, and Management, 2025)
Investment in chemical/oil tankers is crucial for enhancing operational performance and maintaining competitiveness in the global shipping industry. The background of this research is the need to provide solutions to challenges in ship investments that often fail to meet targets, whether in technical performance, compliance with international regulations, or cost efficiency. These conditions affect the competitiveness of companies, as most chemical/oil tanker fleets are over 15 years old, require high maintenance costs, and pose risks of detention by Port State Control (PSC) and rejection by major oil companies. The methodological approach is the integration of Decision-Making Trial and Evaluation Laboratory (DEMATEL) and Analytic Network Process (ANP) to analyze the selection of chemical/oil tanker ship investments. DEMATEL is used to identify cause-effect relationships so that dominant factors can be prioritized. Once the dominant factors are obtained, ANP processes the relationships and dependencies among criteria in the network model and determines more precise weighting. Subsequently, priority calculations are carried out by constructing a supermatrix that encapsulates the relationships among elements. This supermatrix is analyzed to produce final priorities for determining the best alternative. The research data were collected through questionnaires and interviews with stakeholders, including top management and experts. DEMATEL revealed key influencing factors such as Initial Investment, Operating Costs, Regulatory Compliance, Market and Geopolitical Risks, and Technological Risks. These factors are analyzed in the ANP method to obtain a model, network, and pairwise comparisons.